Mitotic defects in fission yeast lipid metabolism 'cut' mutants are suppressed by ammonium chloride - Zach, Róbert; Tvaružková, Jarmila; Schätz, Martin; Tupa, Ondrej; Grallert, Beáta; Prevorovský, Martin (FEMS yeast research, 2018)
Fission yeast 'cut' mutants show defects in temporal coordination of nuclear division with cytokinesis, resulting in aberrant mitosis and lethality. Among other causes, the 'cut' phenotype can be triggered by genetic or chemical perturbation of lipid metabolism, supposedly resulting in shortage of membrane phospholipids and insufficient nuclear envelope expansion during anaphase. Interestingly, penetrance of the 'cut' phenotype in mutants of the transcription factor cbf11 and acetyl-coenzyme A carboxylase cut6, both related to lipid metabolism, is highly dependent on growth media, although the specific nutrient(s) affecting 'cut' occurrence is not known. In this study, we set out to identify the growth media component(s) responsible for 'cut' phenotype suppression in Δcbf11 and cut6-621 cells. We show that mitotic defects occur rapidly in Δcbf11 cells upon shift from the minimal EMM medium ('cut' suppressing) to the complex YES medium ('cut' promoting). By growing cells in YES medium supplemented with individual EMM components, we identified ammonium chloride, an efficiently utilized nitrogen source, as a specific and potent suppressor of the 'cut' phenotype in both Δcbf11 and cut6-621. Furthermore, we found that ammonium chloride boosts lipid droplet formation in wild-type cells. Our findings suggest a possible involvement of nutrient-responsive signaling in 'cut' suppression.
Keywords: Schizosaccharomyces pombe Proteins; chlorid amonný; Culture Media; fenotyp; Phenotype; mutace; Acetyl-CoA Carboxylase; kultivační média; Mitosis; Penetrance; lipidová tělíska; metabolismus lipidů; Schizosaccharomyces; Ammonium Chloride; Transcription Factors; transkripční faktory; Lipid Metabolism; penetrance; Schizosaccharomyces pombe - proteiny; acetyl-CoA-karboxylasa; mitóza; Mutation; Lipid Droplets